The impact of infrastructure planning of complete street elements on the urban environment (Journal of Planner and Development, 2023)
In contemporary cities, the expansion of the use of vehicles has led to the deterioration of the urban environment. To counter this, many concepts and strategies emerged that attempted to regulate mobility in cities and limit its effects. The concept of a "complete street" is one of the modern trends concerned with diversifying means of transportation and reducing the disadvantages of mechanical transportation methods This paper discusses the role that complete streets can play in developing the urban environment in the Alyarmok District of Baghdad, which suffers from traffic congestion and its associated problems.In this study, 104 people were surveyed in the Alyarmok region, and the linear regression method was used to analyze their opinions in order to find the relationship between the urban environment and the complete street elements. This paper concluded that the implementation of a complete street strategy in the study area will lead to the development of urban environments. Whereas 96% of street users believe that the lack of lanes for the elderly and people with special needs reduces the use of active transportation. And that 75% of the sample answered The lack of multiple modes of transportation in the study area makes them dependent on private cars for transportation. And 42% of the street users answered that implementing lanes for people with special needs would encourage them to use active transportation. Also, 32% of the respondents would prefer to implement corridors with multiple modes of transport, which would make them use active transport more than before.